Penanganan Lena pada Departemen Tata Graha di Hotel XYZ - Wiguna, I Nyoman Candra; Seniartha, I Wayan; Sunarsa, I Wayan; Darmawijaya, I Gede (Program Studi Manajemen Divisi Kamar, 2025)
The purpose of this study was to find out how to handle linen in the Housekeeping Department at Hotel XYZ. The data analysis method used is qualitative descriptive. Data collection techniques are applied to obtain data, namely interviews, observations, and documentation studies. Interviews were conducted with executive housekeepers, and observations of the linen attendant officers were made using the observation checklist tool. The results of the study showed that 12% of the handling of linen in the housekeeping department in general was not in accordance with the standard operating procedures set. The advice that can be given is that the linen attendant is expected to supervise the laundry vendor in sorting out dirty linen, pay attention to the FIFO (First In, First Out) system, clean up torn and stained linen, and is expected to clean the linen store periodically